PENGARUH PENGGUNAAN ARTIFICIAL INTELLIGENCE DAN PEMAHAMAN RULES & REGULATIONS TERHADAP AUDIT JUDGMENT - Prasetya, M. Rowi; Anwar, Choirul; Yusuf, Muhammad (Komunitas Menulis dan Meneliti (Kolibi), 2024)
This study aims to examine the influence of Artificial Intelligence (AI) usage and understanding of rules & regulations on audit judgment among auditors at Public Accounting Firms (KAP) in South Jakarta. Using primary data from 69 respondents selected through convenience sampling, the research applies data analysis techniques including measurement model testing, structural model testing, and hypothesis testing using Smart-PLS 4.1. The results indicate that AI usage does not affect audit judgment due to limited AI adoption and auditors' reliance on their own abilities. However, a deeper understanding of rules & regulations significantly influences audit judgment, as it helps auditors adapt to evolving regulations and provide assessments that comply with applicable standards.